2000
DOI: 10.1021/jp993981e
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculation and X-ray Absorption Spectroscopy Studies of Structure of Vanadium-Containing Aluminophosphate VAPO-5

Abstract: Theoretical calculation using density functional B3LYP correlation-exchange is employed to study the structure of different sizes of the VAPO-5 clusters. The results indicate that the substitution of either the phosphorus site or the aluminum site of the aluminophosphate-5 framework with vanadium is generally not feasible. The calculated structures are comparable with those from the in-situ X-ray absorption (XANES and EXAFS) of the V K-edge. The isolated vanadium was found to exist as a mono-oxo (V 4+ ) O)(O f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…19,20,36,37 A major source of complexity associated with studying VAPOs is the vanadium ion's ability not only to adopt different oxidation states, but also to occupy both framework and extraframework positions. Furthermore, V ions in solution can give rise to oligomerisation and yield polynuclear clusters.…”
Section: 263334mentioning
confidence: 99%
See 1 more Smart Citation
“…19,20,36,37 A major source of complexity associated with studying VAPOs is the vanadium ion's ability not only to adopt different oxidation states, but also to occupy both framework and extraframework positions. Furthermore, V ions in solution can give rise to oligomerisation and yield polynuclear clusters.…”
Section: 263334mentioning
confidence: 99%
“…The structure of V ions in AlPOs frameworks is still the subject of an open debate, due to the complex chemistry and coordinative flexibility of the oxovanadium species (V 4+ O or V 5+ O vanadyls), the vanadyl ion being the usual source of vanadium in the VAPO synthesis. ,,, A major source of complexity associated with studying VAPOs is the vanadium ion’s ability not only to adopt different oxidation states but also to occupy both framework and extraframework positions. Furthermore, V ions in solution can give rise to oligomerization and yield polynuclear clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The attempts to optimize representative ring type clusters for each of the structures investigated in this study, following a procedure similar to that described by Cheng et al, 34 was unsuccessful. Here we present the optimized structures derived from the SOD framework, for which all possible rings were investigated.…”
Section: Appendix Amentioning
confidence: 99%
“…The calculated clusters indicated that while the substitution of either P or Al in the framework is not feasible, the parameters of optimized models representing an extraframework substitution site are comparable with those obtained from the in-situ X-ray absorption experiments. 34 In this paper we have examined, using high-field EPR techniques, three Mn(II) incorporated aluminophosphate structures (Mn-AlPO 4 -20, Mn-AlPO 4 -5, and Mn-AlPO 4 -11), two new frameworks composed of magnesium-aluminophosphate with large open cages 8 (Mn-UCSB-6Mg and Mn-UCSB-10Mg) and one example of Fe(III) incorporated into aluminophosphate zeotype (Fe-AlPO 4 -20). These framework structures are schematically presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…18 Padlyak et al showed framework incorporation of the Cr 3+ ions only for CrAPO-5 with high sorption properties. 19 We have studied the structure of a vanadium-containing aluminophosphate-5 molecular sieve (VAPO-5) using the density functional theory (DFT) 20 calculations combined with in-situ XAS 21 and Raman Spectroscopy 22 previously. Results have shown that the substitution of the aluminum or phosphorous site of an AFI framework by vanadium is in general not feasible.…”
Section: +mentioning
confidence: 99%